Retracted: Prevalence of gestational diabetes mellitus and associated risk factors amongst antenatal women attending urban health centre of Rajkot City, Gujarat - Nimavat, Nirav K.; Dadwani, Roma S.; Kartha, Girija P. (International Journal Of Community Medicine And Public Health, 2019)
The article "Prevalence of gestational diabetes mellitus and associated risk factors amongst antenatal women attending urban health centre of Rajkot City, Gujarat" is retracted by the Editor-in-Chief, due to violation of the policies and practices of International Journal of Community Medicine and Public Health. The article is retracted due to dispute in authorship.